Consumer Preference for Buying Beef at the Traditional Market in Magelang City - Hidayah, Lutfi; Hidayati, Sri; Septian, Mohamad Haris (Fakultas Peternakan, Universitas Padjadjaran, 2023)
The purpose of this study was to identify and examine the characteristics and attitudes of consumers preferences towards buying beef in the Traditional Markets of Magelang City, namely Gotong Royong Market, Rejowinangun Market, and Kebonpolo Market. The research was carried out in December 2022. The research method used is descriptive analytic. The number of respondents as many as 100 people with the sampling method that is purposive random sampling. The data obtained were analyzed using the validity test, reliability test, descriptive analysis, and fishbein multi-attribute analysis. The results of the validity test and reliability test show the validity and reliability of all available question items. The research results show that consumer characteristics to be in the age group of 41-65 years, female, senior high school (SMA), work as an entrepreneur, and have a total monthly income of IDR 500,000-IDR 1,500,000. Consumer preference decisions is ruby and chili red meat colors, small amount of fat, top meat parts, and meat prices according to quality. Results fishbein multi-attribute analysis obtained a total score of 61.00, which means that consumers of the Traditional Market in Magelang City fall into the neutral or normal category for beef attributes such as color, amount of fat, portion, and price.